Legal Politics of Sustainable Agricultural Empowerment in South Sulawesi for Community Welfare and Sustainable Development - Bahar Sinring; Andika Prawira Buana (Manunggal Halim Jaya, 2022)
Conventional agriculture is considered to have a negative impact in the form of degradation and a decrease in soil fertility, reducing soil moisture, damaging ecosystems in the surrounding environment, causing erosion, and causing severe problems with consumer health problems. This prompted the Provincial Government of Sulawesi to determine the answer through official state policies. The method used is normative-empirical with a conceptual approach and legislation, focusing on examining primary data obtained through interview techniques and secondary data consisting of primary legal materials and secondary legal materials. The data is classified and analyzed descriptively and exploratory. The results of the study show that the government in formulating policies is carried out by developing regional regulations on organic farming systems that contain norms, including first, planning and implementation; second, organic agricultural production facilities; third, organic farming; fourth, facilitating the marketing of organic farm products; fifth, certification, and labeling; sixth, awards; seventh, community participation; eighth, coaching; ninth, supervision; and tenth, supervision.